Experimental assessment of the utilization of a novel interpenetrating polymer network in different processes in the agricultural sector. Issue 28 (3rd April 2019) - Sharma, Saruchi; Kumar, Vaneet; Pathak, Dinesh; Mittal, Hemant; Alhassan, Saeed M.
ABSTRACT: We synthesized a biodegradable, controlled release formulation via the impregnation of methyl methacrylic acid onto the natural polysaccharide, gum tragacanth, and a polyacrlyic‐based hydrogel with glutaraldehyde as crosslinker. The biodegradation behavior of the prepared interpenetrating polymer network (IPN) was investigated with soil burial and composting methods, and the biodegradability stages were studied with Fourier transform infrared spectroscopy and scanning electron microscopy analyses. The controlled release data of the calcium nitrate was analyzed in accordance with Fick's power law, and the kinetics parameters of the release process were calculated. The values of the initial and lateral diffusion coefficients indicated a fast initial release rate of the fertilizers in comparison to the lateral release. The synthesized IPN was degraded 91.62% within 11 weeks under composting methods, whereas it degraded 78.83% under the soil burial method. The results show that the synthesized IPN was ecofriendly and could be used for the controlled release of agrochemicals. The impact of the degraded IPN on the fertility of the soil was also studied. We concluded from the results obtained that the biodegraded IPN did not have any adverse effects on the soil fertility. Hence, this biodegradable IPN could be of great significance from a green revolution point of view. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47739. Abstract :